Mammographic and ultrasonographic features of benign and malignant phyllodes tumours - Muttarak M. (2014)
Purpose: To present the mammographic and ultrasonographic features of benign and malignant phyllodes tumours, to determine if the tumour can be differentiated from other breast tumours, and whether imaging can be used to differentiate benign from malignant phyllodes tumours. Materials and methods: We retrospectively reviewed the clinical, imaging and pathological findings of 29 phyllodes tumours (23 benign, 6 malignant) in 28 women between February 1994 and October 2000. Mammography was performed bilaterally in all patients except one patient, who had bilateral breast masses. In this patient, the mass in one breast was so large that mammography on this side was not technically possible. Ultrasonography (US) was performed in 23 patients. Of these, colour Doppler US was performed in 14 patients. Computed tomography (CT) of the chest was performed in one patient. Results: Twenty-four patients presented with palpable masses and four patients presented with diffusely enlarged breasts. The patients ranged in age from 24 to 79 years (mean 47.3 years). The tumour diameter varied from 2 to 15 cm (mean 6.43 cm, SD 3.72). The mean diameters of benign and malignant tumours were 6.39 cm (SD 4.02) and 6.60 cm (SD 2.19), respectively. This was not statistically significant (p=0.527). On mammography, 22 tumours were well-defined, round or oval, with smooth or lobulated borders. Five of these masses were malignant. Six benign tumours were seen as ill-defined masses. One benign tumour contained microcalcifications and one malignant tumour contained macrocalcifications. CT of the chest in one patient who had bilateral malignant tumours revealed inhomogeneous enhancing masses in the breasts and lung metastases. On US, 18 benign tumours and 4 malignant tumours had well-circumscribed lobulated margins. One benign tumour had ill-defined margin. All malignant tumours and 15 benign tumours showed inhomogeneous internal echoes. The other 4 benign tumours had homogeneous internal echoes. Intratumoural cystic spaces were seen in 5 benign tumours and one malignant tumour. Intratumoural blood flow was present in both benign and malignant phyllodes tumours. Conclusion: The imaging characteristics of benign and malignant phyllodes tumours overlap. Neither mammography nor US can be used to reliably differentiate malignant from benign phyllodes tumours. Imaging features of a small phyllodes tumour cannot be differentiated from a fibroadenoma and a circumscribed carcinoma. However, a circumscribed large tumour may suggest the diagnosis of a phyllodes tumour.